Parenting styles and coping strategies among patients with early detected and treated congenital hypothyroidism - Pardo Campos, María L. (2018)
Fil: Pardo Campos, María L. Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía; Argentina